2017
DOI: 10.1007/s10072-017-3187-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of olfactory and gustatory disorders in Alzheimer’s disease

Abstract: Patients with Alzheimer's disease (AD) develop olfactory and gustatory disorders. However, the order of failure and relevance of the pathophysiology are unclear. We compared olfactory identification and whole mouth gustation in patients with AD to those with mild cognitive impairment (MCI) and to healthy controls (HC) and assessed correlations with pathophysiology. Patients with AD (n = 40), MCI (n = 34), and HC (n = 40) were recruited. We performed the Odor Stick Identification Test for Japanese (OSIT-J), gus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Moreover, there were no significant differences in the changes in the TDAS, OSIT‐J and PSQI‐J scores from pre‐intervention (week 4) to intermediate intervention (week 16) or post‐intervention (week 28) between the groups (Table ). When the cut‐off point of OSIT‐J was set to ≤7.5 points in reference to the previous research, 31 (88.6%) patients had olfactory disorders at baseline. When the cut‐off point of PSQI‐J was set to ≥5.5 points in reference to the previous research, six (17.1%) patients showed declines in subjective sleep quality from baseline values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there were no significant differences in the changes in the TDAS, OSIT‐J and PSQI‐J scores from pre‐intervention (week 4) to intermediate intervention (week 16) or post‐intervention (week 28) between the groups (Table ). When the cut‐off point of OSIT‐J was set to ≤7.5 points in reference to the previous research, 31 (88.6%) patients had olfactory disorders at baseline. When the cut‐off point of PSQI‐J was set to ≥5.5 points in reference to the previous research, six (17.1%) patients showed declines in subjective sleep quality from baseline values.…”
Section: Resultsmentioning
confidence: 99%
“…Some patients with dementia exhibit olfactory disorders, and there are several reports on olfactory disorders, particularly in patients with Alzheimer's disease (AD) and those with dementia with Lewy bodies (DLB) . Furthermore, it has been reported that patients with mild cognitive impairment (MCI), which is a pre‐dementia state, exhibited olfactory disorders and that MCI patients with severe olfactory disorder exhibited poor memory performance . In addition, it has been reported that amyloid ß, phosphorylated tau and alpha synuclein, which are proteins associated with the pathogenesis of AD or DLB, were deposited in olfactory‐related areas .…”
Section: Introductionmentioning
confidence: 99%
“…Whole‐mouth gustatory and electrogustatory tests were performed. In the whole‐mouth gustatory test, a droplet (about 0.05 mL) of the test solutions was placed on the tongue (in order starting from No.1) as described previously . The concentration of the test solution (Sanwa Kagaku Kenkyusho, Co. Ltd.) is shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…In the whole-mouth gustatory test, a droplet (about 0.05 mL) of the test solutions was placed on the tongue (in order starting from No.1) as described previously. 17 The concentration of the test solution (Sanwa Kagaku Kenkyusho, Co. Ltd.) is shown in Table 1. The order of sweet (S), salty (N) or sour (T) solution was randomised, but bitter (Q) was always administered last.…”
Section: Examinationmentioning
confidence: 99%
“…Weight loss in AD patients could also result from defective sensory (e.g., taste/olfaction) integration or processing [18]. …”
Section: Main Neuroendocrine-metabolic Dysfunction In Admentioning
confidence: 99%